2023
DOI: 10.3389/fpsyg.2023.1071555
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-assisted focus on forms in English for academic purposes instruction: Investigating the impacts on learning academic words

Abstract: Focus on forms (FonFs) is a pedagogical approach in Instructed Second Language Acquisition (ISLA) that emphasizes students’ conscious and direct attention to learning target language features in isolation and outside their meaningful context. FonFs has been employed extensively in foreign language vocabulary instruction, and earlier studies reported positive results for such interventions. The present study investigated mobile-assisted FonFs in the context of English for Academic Purposes (EAP) to address the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Two main approaches exist in the teaching of academic vocabulary: direct and indirect (Huckin & Coady, 1999). The direct approach advocates explicit instructions to increase students' exposure to academic vocabulary (Sibold, 2011;Xodabande & Boroughani, 2023). Corpus studies (Coxhead, 2000;Gardner & Davies, 2014;Kwary & Artha, 2017), which developed or refined academic existing vocabulary lists, often guide teachers' choices of content (Webb & Nation, 2017).…”
Section: Understanding Academic Vocabulary Technical Vocabulary and T...mentioning
confidence: 99%
“…Two main approaches exist in the teaching of academic vocabulary: direct and indirect (Huckin & Coady, 1999). The direct approach advocates explicit instructions to increase students' exposure to academic vocabulary (Sibold, 2011;Xodabande & Boroughani, 2023). Corpus studies (Coxhead, 2000;Gardner & Davies, 2014;Kwary & Artha, 2017), which developed or refined academic existing vocabulary lists, often guide teachers' choices of content (Webb & Nation, 2017).…”
Section: Understanding Academic Vocabulary Technical Vocabulary and T...mentioning
confidence: 99%
“…The findings are presented as below. (Alhebshi & Gamlo, 2022) Quizlet (Aprilani & Suryaman, 2021;Jiang & Liou, 2022;Pham, 2022) Mobile apps (Arumugam & Md Noor, 2021;Jalaluddin et al, 2021;Kohnke, 2020;Polakova & Klimova, 2022;Xodabande and Hashemi, 2022) Mobile devices (Govindasamy et al, 2019;Katemba, 2021;Wijaya et al, 2019;Xodabande & Boroughani, 2023) Quizizz (Huei et al, 2021) Whatsapp (Tahounehchi, 2021) According to the findings presented in Table 4, a total of 5 research articles indicate that mobile applications are the most preferred form of MALL used for vocabulary acquisition (Arumugam & Noor, 2021;Jalaluddin, 2021;Kohnke 2020;Polakova & Klimova, 2022;Xodabande & Hashemi, 2022). The second most favoured type of MALL is the use of mobile devices themselves.…”
Section: Rq 1: What Are the Types Of Mall Used For Vocabulary Acquisi...mentioning
confidence: 99%
“…(Aprilani & Suryaman, 2021;Kohnke, 2020;Pham, 2022) Based on the information presented in Table 5, it is clear that most of the MALL implementations for vocabulary acquisition in the identified articles involve a comparison. A total of 9 articles examines the implementation of MALL tools for vocabulary acquisition and compare them with the traditional approach (Alhebshi & Gamlo, 2022;Arumugam & Md Noor, 2021;Govindasamy et al, 2019;Huei et al, 2021;Katemba, 2021;Tahounehchi, 2021;Wijaya, 2019;Xodabande & Boroughani, 2023;Xodabande & Hashemi, 2022). The use of comparison as the main purpose for MALL implementation is highly favoured due to its ease in evaluating the efficacy of the implemented MALL tool.…”
Section: Rq 2: How Is Mall Implemented For Vocabulary Acquisition?mentioning
confidence: 99%
“…Second, learning (and using) academic words are associated with a considerable learning burden for EFL university students ( Evans and Morrison, 2010 , 2011 ; Xodabande et al, 2022 ; Boroughani et al, 2023 ). In this regard, there is a growing need for a systematic focus on covering these words in EAP programs regardless of the learning context ( Coxhead, 2018 , 2019 ; Xodabande and Boroughani, 2023 ). Additionally, the expanding body of knowledge in corpus-based studies of research articles as the pre-eminent genre in academic discourse has shown the significant role and the importance of academic words in scientific communication ( Martínez et al, 2009 ; Lei and Liu, 2016 ; Xodabande et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the related studies pointed to both short- and long-term learning impacts of mobile-assisted instruction ( Xodabande and Atai, 2022 ). Considering the effectiveness of flashcards (or word cards) in fast and effective vocabulary learning ( Nakata, 2019 ; Lei and Reynolds, 2022 ), mobile-assisted academic vocabulary learning via digital flashcards is gaining popularity ( Dizon, 2016 ; Xodabande et al, 2022 ; Xodabande and Atai, 2022 ; Yüksel et al, 2022 ; Boroughani et al, 2023 ; Xodabande and Boroughani, 2023 ). Collectively, these studies showed that digital flashcards provide university students with affordances for augmenting their vocabulary knowledge more systematically and beyond the physical and temporal restraints of the classrooms.…”
Section: Introductionmentioning
confidence: 99%